When microclimates meet soil microbes: Temperature controls soil microbial diversity along an elevational gradient in subtropical forests. (March 2022) - Ma, Luwen; Liu, Lan; Lu, Yaoshun; Chen, Lin; Zhang, Zhaochen; Zhang, Hongwei; Wang, Xiaoran; Shu, Li; Yang, Qingpei; Song, Qingni; Peng, Qiaohua; Yu, Zeping; et al.
Abstract: Climatic variability along elevational gradients affects biodiversity and produces a natural range of conditions for realistic experiments. Soil biodiversity is expected to respond to the general climatic conditions, as well as microclimatic effects. With the Illumina MiSeq high-throughput sequencing technique, we systematically examined the taxonomic and phylogenetic diversity of soil bacteria and fungi along a 320-1350 m elevational gradient in subtropical forests. Microclimate data under continuous in-situ monitoring, soil physicochemical properties, and plant composition attributes were collected in the forest sites. We found a contrasting pattern in soil bacterial and fungal taxonomic diversity, with monotonically decreasing bacteria populations and no obvious change in fungi taxonomic richness but increased Shannon-Wiener index with increasing elevation. However, the analysis of the richness-dependent phylogenetic index showed no bacterial phylogenetic variability across the elevation gradient, whereas fungal phylogenetic variability increased with greater elevation. Soil temperature and pH were strongly associated with bacterial diversity, but less well correlated with fungal diversity. Microbial community structure differed taxonomically and phylogenetically along the elevation gradient and was most strongly related to soil temperature, followed by soil variables such as soil pH and N content. We conclude that microclimates are ecologically significant in mediating soil microbial community assembly. Highlights: Soil bacteria and fungi have distinct diversity patterns along an elevational gradient. Microclimates affect the ecology and evolution of montane soil microbes. Scale-relevant environmental data is essential in biodiversity studies.